Respostas

2014-02-15T18:31:01-02:00
1) a) 7 + 3 (4-5) - 8 . 9 - (7-7) + 20 - 13 = 
        7 + 3 . (1) - 72 - 0 + 20 - 13=
          7 + 3 - 72 + 20 - 13 = - 55

 b) 9 . 5 - (6-3) + (9-11) + 45 - 37 = 
     45 - 3 + (-2) +45 - 37= 
      42 - 2 + 8 = 48

 c) 35 - 18 + 23 - 40 + 9 - 7 - (-6+12) =
      35 - 18 + 23 - 40 + 9 - 7 - 6 = - 4

2) a) x + 2x - 10 = - (x-4) - 20  
         x + 2x - 10 = - x + 4 - 20
           x + x + 2x = 4 - 20 +10
            4x = - 6 
             x = - 6 / 4 .: x = - 1,5

 b) 5x + 49 - 5 . 0 = 2x + 14
     5x - 2x = 14 - 49
       3x = - 35
         x = - 35 / 3
       
1 5 1